An approach for including heat pump performance in the design of thermo-active piles - Provost,A; Sanchez,Fernandez J; Sapin,P; Taborda,D (ISSMGE, 2025)
The focus on sustainable built environment has grown with the drive for net-zero. The use of pile foundations and other geotechnical structures as ground heat exchangers (GHEs) is key to unlocking the economic viability of ground-source energy systems (GSESs) in dense urban areas. However, current design procedures characterise the performance of GHEs under a given temperature or heat flux, which consider the heat exchanger in isolation from the rest of the GSES. This study proposes a new method to assess the thermal performance of GHEs based on the electricity consumption of the heat pump byintroducing explicitly a model describing its performance based on operating temperatures. This general method is applied to a thermo-active pile, providing insights into the impact of pile diameter and length